Two new species of Collybiopsis (Agaricales, Omphalotaceae) from Beijing, China - Yang, Wen-Qiang; Zhang, Jia-Rui; Cao, Man-Ting; Hu, Zuo-Lu; Zhao, Rui-Lin (Phytotaxa, 2025)
Collybiopsis (Omphalotaceae, Agaricales) is a genus of a worldwide distribution, which are often growing on dead leaves or decaying wood in forests or grassland, and some of them were reported as edible or poisonous species. In this study 28 specimens of Collybiopsis were collected from Baihuashan National Natural Reserve in Beijing, China. All specimens were identified through morphological examination, and phylogenetic analysis using ITS and nrLSU sequences. The results revealed two new species, which named as C. beijingensis and C. lignicola. Both new species were described in details and compared with closely related known species in morphology.